INFLUENCE OF PIRDOT LEAF (SAURAUIA VULCANI, KORTH.) EXTRACT ON THE BLOOD GLUCOSE RATE AND HISTOLOGIC DESCRIPTION OF THE RETINA OF MALE MICE (MUS MUSCULUS STRAIN DDW) - Hutapea, Adiluddin; Hutahaean, Salomo; Ilyas, Syafruddin (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: This research aims to collect laboratory data on the influence of pirdot leaf extract on the retina and blood glucose rate. Method: The mice were classified into 5 groups: A control group without any treatment, a control group treated with a single injection of 125 mg/kg body weight (BW) of alloxan as the diabetes mellitus trigger, and three groups treated with intra-muscular alloxan injection to induce diabetes mellitus, and pirdot leaf extract, i.e., 150 mg/kg BW (P1), 200 mg/kg BW (P2), and 250 mg/kg BW (P3) for 8 weeks. Subsequently, the blood glucose rates of the mice were measured, and histologic grazes of their retina layers were prepared using the paraffin method. Results: The blood glucose rate of the mice treated with 200 mg/kg BW (113.4 mg/dl) pirdot leaf extract significantly differed from that of the mice in the diabetes mellitus control group (364.8 mg/dl) (p<0.05). The ganglion cell layer of the retina increased by up to 7.59 Î¼m, which differed from that of the diabetes mellitus group (3.67 Î¼m) (p<0.05) treated with 250 mg/kg BW pirdot leaf extract. The external plexiform layer increased to 17.88 Î¼m, which differed from that of the diabetes mellitus group (15.71 Î¼m) (p<0.05) treated with 150 mg/kg BW pirdot leaf extract. Conclusion: The blood glucose rate obtained after treatment with pirdot leaf extract was lower than that of the diabetes mellitus control group.